AN ANTHOLOGY OF THE DISTINGUISHED ACHIEVEMENTS IN SCIENCE AND TECHNIQUE. PART 44: TRADITIONAL POWER ENGINEERING. NUCLEAR POWER STATIONS: RETROSPECTIVE VIEW, STATE AND PROSPECTS OF THEIR DEVELOPMENT - M. I. Baranov (National Technical University "Kharkiv Polytechnic Institute", 2018)
Purpose. Preparation of brief scientific and technical review about a retrospective view, modern state, achievements, problems, tendencies and prospects of development of world nuclear energy. Methodology. Known scientific methods of collection, analysis and analytical treatment of the opened scientific and technical information, present in scientific monographs, journals and internet-reports, world level in area of nuclear energy. Results. A brief analytical scientific and technical review is resulted about a retrospective view, modern state, basic achievements, existent problems, tendencies and prospects of development of nuclear energy in the industrially developed countries of the world. Considerable progress is marked in development and creation of technical base of modern nuclear energy, including the nuclear power stations (NPP) such their basic devices as nuclear reactors, steam generators, steam turbines and turbogenerators. The basic charts of construction of NPP producing in the world now about 11 % are described annual production electric power. It is indicated that in Ukraine a production of electricity volume at NPP makes more than 50 %, and in France − more than 70 % in annual power balance of country. Nuclear-physical bases of work of nuclear reactor are resulted on thermal-neutron, widely in-use at NPP. The design of most safe water-waters of nuclear power-reactor of type of WWER-1000 is described by thermal power 1000 MW, applied presently at NPP of Ukraine. Basic classification of nuclear reactors is presented. Technical information is resulted about largest NPP of the world. Master data are indicated about a nuclear fuel and radio-active offcuts of nuclear reactors of NPP. Basic measures and facilities are described for the increase of safety of nuclear reactors and NPP. Advantages and lacks of NPP are marked by comparison to the thermal power plants. Nuclear energy of Ukraine is considered and basic technical descriptions of operating domestic NPP are indicated. Basic problems, tendencies and possible prospects of development, are marked in the world and to Ukraine of nuclear energy. Originality. Systematization of the scientific and technical materials touching functioning of such important sector of world economy as nuclear energy known from the sources opened in outer informative space is executed. It is shown on the basis of approach of the systems that in spite of row of existent problems in area of world nuclear energy has the real prospects in the further development and to service society at satisfaction of his increasing requirements in electric and thermal energies. Practical value. Popularization and deepening for students, engineer-technical and scientific workers of scientific and technical knowledge in area of modern nuclear physics and energy, extending their scientific range of interests and further development of scientific and technical progress in society.